2009
DOI: 10.1111/j.1365-2567.2008.02977.x
|View full text |Cite
|
Sign up to set email alerts
|

The lectin Jacalin induces human B‐lymphocyte apoptosis through glycosylation‐dependent interaction with CD45

Abstract: SummaryIt has been well established that CD45 is a key receptor-type protein tyrosine phosphatase (PTPase) regulating Src-family protein tyrosine kinase (Src-PTK) in T and B lymphocytes. However, precisely how CD45 exerts its effect in these lymphocytes remains controversial. We recently reported that Jacalin, an a-O-glycoside of the disaccharide Thomsen-Friedenreich antigen-specific lectin from jackfruit seeds, caused marked T-cell activation in response to T-cell receptor ligation and CD28 costimulation by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…The lectin like domain in natterin is homologous to Jacalin domain identified in jack fruit. Little work has been done on natterin in fish but jacalin, the plant homologue, is reported to be involved in activation of human T- lymphocytes [24] and apoptosis of B-lymphocytes [25] suggesting a role in the immune system of fish. In mucus the lectin domain could give direct interaction with pathogens and the pore forming toxin domain could potentially result in lysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lectin like domain in natterin is homologous to Jacalin domain identified in jack fruit. Little work has been done on natterin in fish but jacalin, the plant homologue, is reported to be involved in activation of human T- lymphocytes [24] and apoptosis of B-lymphocytes [25] suggesting a role in the immune system of fish. In mucus the lectin domain could give direct interaction with pathogens and the pore forming toxin domain could potentially result in lysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some plant lectins, such as those of mistletoe, which also bind specifically through lactose or galactose, bring about caspase‐dependent apoptosis through mitochondria and/or death receptors of human tumour cells (12,13,36) and apoptosis of K562 cells caused by a D‐galactose lectin (CvL) via a caspase‐independent mechanism, has been reported (30). A Galβ1‐3Gal‐NAc‐binding lectin (Jacalin) from jackfruit seeds inhibited CD45 tyrosine phosphatase activity of human B lymphocytes resulting in apoptosis (37). Thus, molecular mechanisms of lectin‐induced apoptosis of tumour cells seems to be complex and cannot be judged simply by carbohydrate‐binding property of lectins.…”
Section: Discussionmentioning
confidence: 99%
“…Jacalin induces B cell apoptosis, resulting in calcium mobilization and calpain activation, suggesting that the calcium-calpain pathway may mediate the Jacalininduced apoptosis. The apoptosis is blocked by a specific CD45 PTPase inhibitor, indicating that Jacalin induces B cell apoptosis through CD45 triggering [85]. In T cells, this lectin bound to CD45 caused an increase in T-cell activation in response to T-cell receptor ligation and CD28 co-stimulation [86].…”
Section: Cd45 Ligands Induce Apoptosismentioning
confidence: 94%
“…Recently, Ma et al [85] reported that the lectin Jacalin induces apoptosis in B cells through glycosylation-dependent interaction with CD45. Jacalin is a Thomsen-Friedenreich antigen-specific lectin from jackfruit seeds that could be a major receptor for CD45 isoforms on B lymphocytes.…”
Section: Cd45 Ligands Induce Apoptosismentioning
confidence: 99%